Ответы и объяснения

Лучший Ответ!
2014-04-01T14:23:12+04:00
X²+ \sqrt{x^{2}-3 }  = 5
 \sqrt{ x^{2} -3}  = 5-x²

ОДЗ:
(5-x²)≥0
(x²-5)≤0
   +           -           +
--------------------------->
      -√5           √5
x∈[-√5; √5]

Возводим обе части уравнения в квадрат:
x²-3=(5-x²)²
Заменим x²=а, получим:
a-3=(5-a)²
a-3=25-10a+a²
-a²+11a-28=0
a²-11a+28=0
D=9=3²
a1=7   или   a2=4

Значит,
x²=√7                                или                   x²=√4
не удовлетворяет ОДЗ                            x1=2 или x2=-2

Ответ: -2; 2